Psychological assessment of atopic dermatitis in Asia: a systematic review - Ishak, Nurhafidah; Mukhtar, Firdaus; Munawar, Khadeeja; Coudhry, Fahad Riaz; Roy, Mollika; Jalal, Farah Atiqah; Choi, Chong Seng (Informa UK Limited, 2022)
Atopic dermatitis (AD) is a frequently occurring skin disorder in Asia that substantially impacts the social, financial, and psychological lives of individuals. However, there is uncertainty regarding the psychological instruments for this domain. Hence, this review systematically assessed the existing measurement instruments used, developed, and/or validated for the measurement of psychological outcomes in Asian adult patients with AD as well as the scope of those assessment tools (e.g. validity and reliability). Electronic searches were performed using six databases (inception to February 2020) to identify studies. Thematic analysis of 44 included studies revealed that the commonly employed tools to assess the quality of life were the Dermatology Life Quality Index followed by the Skindex-16 questionnaire, the European Quality of Life-5 Dimensions, and the Quality of Life Hand Eczema Questionnaire. Similarly, the Patient Health Questionnaire, Self-rating depression scale (SDS), and Hospital Anxiety and Depression Scale were frequently employed to assess depressive symptoms. Additionally, symptoms of anxiety were frequently assessed through Interaction Anxiousness Scale and the Spielberger State-Trait Anxiety Inventory. Although a variety of psychological assessment measures have been used in research, data on their reliability and validity is limited. Also, information on the cultural applicability of these instruments is scantier. More research is needed to ascertain the suitability of tools for use in clinical practice.